Human‐simulation‐based learning to prevent medication error: A systematic review. Issue 1 (31st January 2018) - Sarfati, Laura; Ranchon, Florence; Vantard, Nicolas; Schwiertz, Vérane; Larbre, Virginie; Parat, Stéphanie; Faudel, Amélie; Rioufol, Catherine
Abstract: Rationale, aims and objectives: In the past 2 decades, there has been an increasing interest in simulation‐based learning programs to prevent medication error (ME). To improve knowledge, skills, and attitudes in prescribers, nurses, and pharmaceutical staff, these methods enable training without directly involving patients. However, best practices for simulation for healthcare providers are as yet undefined. By analysing the current state of experience in the field, the present review aims to assess whether human simulation in healthcare helps to reduce ME. Methods: A systematic review was conducted on Medline from 2000 to June 2015, associating the terms "Patient Simulation, " "Medication Errors, " and "Simulation Healthcare." Reports of technology‐based simulation were excluded, to focus exclusively on human simulation in nontechnical skills learning. Results: Twenty‐one studies assessing simulation‐based learning programs were selected, focusing on pharmacy, medicine or nursing students, or concerning programs aimed at reducing administration or preparation errors, managing crises, or learning communication skills for healthcare professionals. The studies varied in design, methodology, and assessment criteria. Few demonstrated that simulation was more effective than didactic learning in reducing ME. This review highlights a lack of long‐term assessment and real‐life extrapolation, with limited scenarios and participant samples. These various experiences, however, help in identifying the key elements required for an effective human simulation‐based learning program for ME prevention: ie, scenario design, debriefing, and perception assessment. The performance of these programs depends on their ability to reflect reality and on professional guidance. Conclusion: Properly regulated simulation is a good way to train staff in events that happen only exceptionally, as well as in standard daily activities. By integrating human factors, simulation seems to be effective in preventing iatrogenic risk related to ME, if the program is well designed.